Anti-bullying programs and Information and Communication Technologies (ICTs): A systematic review. (July 2015) - Nocentini, Annalaura; Zambuto, Valentina; Menesini, Ersilia
Abstract: Information and Communication Technologies (ICTs) constitute suitable tools for interventions with children and adolescents promoting their emotional, psychological and social wellbeing. Recently, in the field of bullying and cyberbullying prevention, some programs started to be implemented using the benefits offered by the virtual environments. The current paper aims to carry out a systematic review on anti-bullying ICT-mediated intervention, analyzing the characteristics of the main programs and the evidence of their effectiveness. The review conducted on three databases (PsycINFO, Scopus and PubMed) yielded 32 full text papers finally evaluated. Overall, considering the enormous development of digital tools and the importance of this experience for young students, the review underlines that ICT tools are generally under-used in prevention and intervention against bullying and cyberbullying (13 programs emerged from the search). In recent years some advances in this direction can be found with the use of different ICTs (serious game, virtual reality, online platforms, internet activities, technological solution). The need for scientific studies on the effectiveness of these virtual interventions is evident from this review and necessary in order to assist practitioners, policy makers, and administrators in deciding which interventions can work or not and why.